2013
DOI: 10.1111/asj.12033
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects explained by variations in the bovine PLAG1 and NCAPG genes on daily body weight gain, linear skeletal measurements and carcass traits in Japanese Black steers from a progeny testing program

Abstract: The c.1326T>G single nucleotide polymorphism (SNP) in the NCAPG gene, which leads to an amino acid change of Ile442 to Met442, was previously identified as a candidate causative variation for a bovine carcass weight quantitative trait loci (QTL) on chromosome 6, which was associated with linear skeletal measurement gains and daily body weight gain at puberty. Recently, we identified the stature quantitative trait nucleotides (QTNs) in the PLAG1-CHCHD7 intergenic region as the causative variations for another c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
7
36
1
1
Order By: Relevance
“…These results of CWT and REA were consistent with data obtained in previous study in the Kagoshima prefecture population [7], and thus confirmed that the NCAPGc. 1326T>G SNP is a causative variation for bovine CWT [2].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…These results of CWT and REA were consistent with data obtained in previous study in the Kagoshima prefecture population [7], and thus confirmed that the NCAPGc. 1326T>G SNP is a causative variation for bovine CWT [2].…”
Section: Resultssupporting
confidence: 92%
“…The observed and expected heterozygosity values at the SNP conformed to the Hardy-Weinberg equilibrium in the Niigata prefecture population. Statistically significant difference was detected between the allele frequencies obtained in the half-sib progeny steers in the Niigata prefecture population and obtained in Japanese Black cattle population of the Kagoshima prefecture [7]. The frequency of the favorable G allele of the c.1326T>G SNP in the Niigata prefecture population was lower than that of the Kagoshima prefecture population.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations